PENERAPAN SANKSI ADAT BAGI ORANG YANG BERZINA MENURUT HUKUM ADAT PADA MASYARAKAT TANAH BEKALI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI - Rahmawan Mulya Sanah; Zulfikar Jayakusuma; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Customary law is a living law because it embodies the real legal feelings of the people.According to Islamic law, adultery is any act or sexual intercourse (male genitals have enteredthe female genitalia) that are carried out outside of marriage. The application of customary lawagainst adulterers, especially in Tanah Bekali Village, Pangean District, Kuantan SingingiRegency. The main problems in this study are: first, what are the rules of adultery based on thecustomary law of the Tanah Bekali community, Pangean District, Kuantan Singingi Regency?Second, how is the settlement of adultery cases before carrying out a marriage in the village ofTanah Bekali, Pangean District, Kuantan Singingi Regency?This research is sociological legal research, namely research that is carried out directlyon the location or in the field to obtain data to provide a complete and clear picture of theproblem being studied, this research was conducted in Tanah Bekali Village, Pangean District,Kuantan Singingi Regency. The sample population is all parties related to the problems studiedin this study. The data sources used are primary data sources and secondary data. Datacollection techniques used, interviews and literature review.From the results of the study there are two main problems that can be concludedFirst, the Adat of Tanah Bekali Village, Pangean District, Kuantan Singingi Regency is anunwritten rule of life, customary sanctions or fines given to perpetrators of adultery accordingto customary law in Tanah Bekali village, namely Didoro or at 100 o'clock. sticks, married,ostracized from society, expelled from the village. Second, the problem of adultery in TanahBekali village is resolved with several levels of settlement that have been determined accordingto customary law in force in Tanah Bekali village, namely: family settlement or mamak soko,settlement by deliberation with Ninik Mamak and community leaders. To prevent the occurrenceof adultery, the ninik-mamak in Tanah Bekali village should be more active in guiding andteaching the applicable customary rules/stipulations, so that awareness and communitycompliance with customary rules will be created. It is better for the people of Tanah Bekalivillage to make village rules that prohibit teenagers or young people from carrying out activitiesuntil after 10 pm except for activities that are indeed held by the village or school, so that thingsdo not happen that are beyond our control and prevent damage to the younger generation..Keywords : Customary Law – Adultery – Customary Sanctions